PENANGANAN COMPLAINT OLEH WAITERS DI CAFÉ HARRIS RESORT WATERFRONT BATAM - Deswita Kezia Sitompul; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Hotel is one of the tourism industry businesses that prioritizes professional service. The quality of appropriate facilities and services is the main thing that is seen by guests who stay. Therefore, every hotel property always updates the service standards and existing facilities. With this, guests who stay overnight will not give complaints. HARRIS Resort Waterfront Batam is a 4-star hotel that always provides innovation and the best service. Harris Café is part of the HARRIS Resort Waterfront Batam which is under the auspices of the Food and Beverage service department which is one of the parts that play a role in providing services. Harris Café is a part that cannot be separated from guest complaints. This is due to the lack of responsiveness of the waiter to the problems experienced by guests. By using the 4 indicators Hear Them out, Empathize, apologize, and Taking proper action and follow up the waiter is expected to be able to handle guest complaints using these indicators. The results of the study show that the waiter has implemented the HEAT method by listening carefully to guest complaints, and empathizing with what the guest is experiencing. The waitress also apologizes and takes further action in handling the guest's complaint. Keywords: Complaints, Waiters